Optimization of Sugarcane Bagasse Ash for Paving Blocks Production - Helgananta Adirya Sabian; Mutiara Rengganis Nurul Putri Azhari; Maktum Muharja (JOBC, 2023)
One of the sugar industries produces large quantities of bagasse ash. Sugarcane bagasse ash in the sugar industry cannot yet be utilized. Sugarcane bagasse ash has a relatively high silica content, namely 68.5%, which can be used as a substitute material to reduce the use of cement in making paving blocks. In this research, concrete bricks were made using the manual pressing method. Paving blocks are made from sand, cement, bagasse ash, stone ash, and water. The cement, stone ash, and sand ratio is 1:2:6, with variations in bagasse ash of 10, 20, and 30% of the sand composition. The test results showed that the highest quality concrete bricks were on the 7th day of drying, with 214 kg/cm2, getting quality B based on SNI 03-0691-1996, and the compressive strength of the resulting concrete bricks would increase as the drying time increased. This innovation can improve the usability of bagasse ash and become a new business opportunity for the sugar industry.